Preferences and Distribution of Feed Sources of Long-Tailed Macaque (Macaca fascicularis) at Utilization Block of Kerandangan Nature Tourism Park - Andriyani, Anis Octa; Syaputra, Maiser; Wahyuningsih, Endah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The preservation of the long-tailed macaque's natural food supplies is one way to help conservation efforts for the species, as it ensures that there are enough food sources to sustain its survival. Managers can implement habitat development through food source augmentation when food supplies are scarce. This study aims to determine the food preferences of long-tailed monkeys and also to determine the plants that are the food sources of long-tailed macaque. The research method uses the line transect method to determine the presence of long-tailed macaque, and the distribution of food sources uses the grid line method. The results found that the food tree with the highest level of use 29% (the most consumed part is fruit) is (Diospyros macrophylla) and the lowest (gmelina arborea) 2% (the part consumed is young leaves/shoots). The most consumed part of the plant is fruit 51%, followed by leaves 47%, and flowers 2%, indicating a tendency for frugivory. Feeding activities are carried out at three main times: morning (06.35 – 10.45), afternoon (12.07 – 15.00), and evening (15.00 – 16.15) following a diurnal pattern, (Tamarindus indica), (Artocarpus heterophyllus), and (Pterospermum javanicum) have a high level of mastery based on the INP. Long-tailed macaque food trees in the Kerandangan TWA Utilization Block have a clustered pattern, with a Morisita Index value for all observed species. Conclusion, regular monitoring of the population and food sources of long-tailed macaque food is needed in the future to see the ecological dynamics that occur.